3D halos assembled from Fe3O4/Au NPs with enhanced catalytic and optical properties. Issue 43 (29th October 2019) - Cai, Ren; Yang, Dan; Lin, Keng-Te; Cao, Thai Son; Lyv, Yifan; Chen, Kangfu; Yang, Yu; Ge, Jia; Xia, Lian; Christou, George; Zhao, Yuliang; Chen, Zhuo; et al.
Abstract : 3D halos were fabricated from co-assembly of Fe3 O4 and Au NPs of different sizes and shapes by a bottom-up strategy, creating new opportunities to explore assembled materials with enriched functionalities. Abstract : 3D structures assembled from multiple components have attracted increasing research interest based on their enriched functionalities and broadened applications. Here, we report a bottom-up strategy to fabricate 3D halos through the co-assembly of Fe3 O4 and Au nanoparticles (NPs). Typically, Fe3 O4 NPs assemble into a 3D core (size around 500 nm) with simultaneous growth of Au NPs on the 3D surface during the assembly process. As a general approach, a variety of 3D halos were fabricated from the co-assembly of Fe3 O4 and Au NPs of different sizes and shapes. To demonstrate the advantages of these 3D halo structures, their catalytic activity to mimic natural enzymes was investigated. Compared with Fe3 O4 NP building blocks, enhanced catalytic efficiency was achieved by the 3D halos. In addition, the optical behavior of the 3D halos was simulated using a three-dimensional finite-difference time-domain (3D-FDTD) method. As shown in the results, the 3D halos attached to 90 nm Au NPs could absorb more incident light owing to high electric field intensities, making these structures promising for applications in energy harvesting and detection-related fields.